Prevalence of Workplace Microaggressions and Racial Discrimination: A Systematic Review and Meta-analysis - Nader Salari; Ahoura Fattah; Amin Hosseinian-Far; Mojdeh Larti; Sina Sharifi; Masoud Mohammadi (Elsevier, 2024)
Background: In recent years, the rise of workplace racial discrimination and microaggressions has decreased the efficiency and productivity of organizations and institutions, and realization of organizational goals globally. Accordingly, it was decided to conduct a systematic review and meta-analysis in the present study with the aim of investigating the prevalence of microaggression and racial discrimination in the workplace. Methods: The PubMed, Scopus, Web of Science, ScienceDirect and Google Scholar databases were systematically searched for studies that had reported the effects of work stress among managers. The search did include a lower time limit and was conducted in June 2023. The heterogeneity of the studies was investigated using the I2 index, and accordingly random effects method was adopted for meta-analysis. Data analysis was conducted with the Comprehensive Meta-Analysis (v.2) software. Results: In the review of seven studies with a sample size of 2998 people, the overall prevalence of microaggression and racial discrimination in the workplace was found to be 73.6% and 18.8%, respectively. Publication bias within the selected studies was examined with the Egger's test, which indicated the absence of publication bias for the pooled prevalence of workplace microaggression (p: 0.264) and for the pooled prevalence of workplace racial discrimination (p: 0.061). Conclusion: The results obtained from this report indicate the high impact of micro-aggression and racial discrimination in the workplace. Considering the negative effects of such behaviours, the findings from this study will be helpful to managers and health policymakers.